STRATEGI INTELEKTUAL MUSLIM DALAM PERSPEKTIF ISLAM DAN MODERNISASI - Mulkhan, Abdul Munir (Jurnal Bestari, 1994)
Nothing more dangerous than science and technology but fading faith and 'half-way' understanding of God's revelation. Consequently, ijtihad and tajdid movement are trapped in ideological and theological matters. Furthermore, the refusal of the modern knowledge tradition to use the scientific methodology developed in the West since long time ago is a dilemma of Islamic thought. Now, however, intellectual Moslems try to revive with their strategies to break through the challenges of modernization